Artists activating sustainability the Oregon story - Sellers-Young, Barbara ca. 20./21.Jh (Anthem Press, 2023)
Examines the way in which the artists within specific communities, against the background of landscape and history, reveal concepts of sustainability that help us broaden our knowledge of what is needed to create a sustainable world